THE INFLUENCE OF PRODUCT QUALITY AND PRICES ON CONSUMER SATISFACTION AT UPTOWN BREW COFFEE SHOP, GREENLAKE CITY, TANGERANG - Linda Desafitri RB; Irfal Irfal; Novita Widyastuti; Ira Mayasari (Universitas Islam Lamongan, 2023)
This research aims to determine the effect of product quality and price on consumer satisfaction at the Uptown Brew coffee shop, Greenlake City, Tangerang. This type of research is quantitative descriptive with multiple regression analysis methods. Accidental Sampling sampling technique. The population in the study was all visitors who came to the Uptown Brew Coffee Shop, Greenlake City, Tangerang. Meanwhile, the sample numbered 100. The partial research results show that product quality and price have a significant effect on consumer satisfaction. Good product quality influences consumer satisfaction, creates customer loyalty, and strengthens the coffee shop brand reputation. Affordable and competitive prices can increase consumer satisfaction by making access easier, offering comparable value, and providing choice.